1982
DOI: 10.1159/000260588
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flow Rate on the Ionized Calcium Concentration of Human Parotid Saliva

Abstract: The ionized calcium concentration of parotid saliva collected at six preselected flow rates ranging from 0.13 to 2.00 ml/min was determined using an ionselective electrode. Total calcium, protein, pH value and ionic strength were also measured. Three experiments were carried out on each of 5 subjects. Increases of total calcium from 0.70 to 1.17mmol/l and ionized calcium from 0.31 to 0.50 mmol/l were noted. Concentrations of ionized calcium and total calcium were significantly correlated (r = 0.83), and the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Many studies revealed the relationship between the amount and components of saliva and some diseases. As the flow rate in parotid saliva of normal people grew more and more in amount, the concentrations of the total protein, calcium and sodium increased 2,3) . The flow rate of the patients suffering from chronic parotitis decreased in comparison with that of normal healthy people 4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies revealed the relationship between the amount and components of saliva and some diseases. As the flow rate in parotid saliva of normal people grew more and more in amount, the concentrations of the total protein, calcium and sodium increased 2,3) . The flow rate of the patients suffering from chronic parotitis decreased in comparison with that of normal healthy people 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Oleo Sci. 57, (2) 115-121 (2008) with the mucous proteins 2,3,22) . As mentioned above, protein and lipids, which have the high molecular weight, reduce the reabsorption of them through the acinar cells in parotid gland, so that lipids and protein in parotid saliva showed upward tendency of concentration in proportion to the increase of the flow rate.…”
mentioning
confidence: 99%
“…Previous studies have shown that one part of salivary calcium secretion takes place bound to proteins like -amylase, which is secreted in zymogen granula by exocytosis. The other part is secreted as free Ca 2+ (Lagerlof and Ekstrand 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Since total and ionized calcium and protein tend to be secreted concomitantly by adult rat and human parotid and submandibular glands (Wallach and Schramm, 1971;Lagerlof and Ekstrand, 1982;Maier et al, 1983), the P-adrenoceptors may therefore play the most important role in the regulation of calcium secretion. The 13-adrenergic receptor contains both the ligand binding site and the site responsible for mediating stimulation of adenylate cyclase activity.…”
Section: Discussionmentioning
confidence: 99%